The role of exercise-induced peripheral factors in sleep regulation - Xiao Tan; Lieve T. van Egmond; Jonathan Cedernaes; Christian Benedict (Elsevier, 2020)
Background: Recurrently disrupted sleep is a widespread phenomenon in our society. This is worrisome as chronically impaired sleep increases the risk of numerous diseases that place a heavy burden on health services worldwide, including type 2 diabetes, obesity, depression, cardiovascular disease, and dementia. Therefore, strategies mitigating the current societal sleep crisis are needed. Scope of review: Observational and interventional studies have found that regular moderate to intensive exercise is associated with better subjective and objective sleep in humans, with and without pre-existing sleep disturbances. Here, we summarize recent findings from clinical studies in humans and animal experiments suggesting that molecules that are expressed, produced, and released by the skeletal muscle in response to exercise may contribute to the sleep-improving effects of exercise. Major conclusions: Exercise-induced skeletal muscle recruitment increases blood concentrations of signaling molecules, such as the myokine brain-derived neurotrophic factor (BDNF), which has been shown to increase the depth of sleep in animals. As reviewed herein, BDNF and other muscle-induced factors are likely to contribute to the sleep-promoting effects of exercise. Despite progress in the field, however, several fundamental questions remain. For example, one central question concerns the optimal time window for exercise to promote sleep. It is also unknown whether the production of muscle-induced peripheral factors promoting sleep is altered by acute and chronic sleep disturbances, which has become increasingly common in the modern 24/7 lifestyle.